2016
DOI: 10.1002/tea.21378
|View full text |Cite
|
Sign up to set email alerts
|

The impact of physics teachers’ pedagogical content knowledge and motivation on students’ achievement and interest

Abstract: This paper examines students' achievement and interest and the extent to which they are predicted by teacher knowledge and motivation. Student achievement and interest are both considered desirable outcomes of school instruction. Teacher pedagogical content knowledge has been identified a major predictor of student achievement in previous research, whereas teacher motivation is considered a decisive factor influencing students' interest. So far, however, most research either focused on knowledge or motivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(184 citation statements)
references
References 112 publications
5
131
0
16
Order By: Relevance
“…A high PCK has been found to ensure a high cognitive activation in the context of physics instructions (Keller et al, 2017), and on the level of reform-based science teaching in biology classrooms (Park et al, 2011). For elementary math teachers, a positive influence of content knowledge for teaching (a blend of CK and PCK) on student learning has been confirmed (Hill et al, 2005) and secondary-level math teachers' PCK was found to influence students' learning directly and mediated through cognitive activation (Baumert et al, 2010).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A high PCK has been found to ensure a high cognitive activation in the context of physics instructions (Keller et al, 2017), and on the level of reform-based science teaching in biology classrooms (Park et al, 2011). For elementary math teachers, a positive influence of content knowledge for teaching (a blend of CK and PCK) on student learning has been confirmed (Hill et al, 2005) and secondary-level math teachers' PCK was found to influence students' learning directly and mediated through cognitive activation (Baumert et al, 2010).…”
Section: Introductionmentioning
confidence: 82%
“…Research has shown that teachers' professional knowledge positively affects instructional quality and thus student learning (Baumert et al, 2010;Heller, Daehler, Wong, Shinohara, & Miratrix, 2012;Hill, Rowan, & Ball, 2005;Keller, Neumann, & Fischer, 2017;Park, Jang, Chen, & Jung, 2011;Roth et al, 2011). A high PCK has been found to ensure a high cognitive activation in the context of physics instructions (Keller et al, 2017), and on the level of reform-based science teaching in biology classrooms (Park et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Very high Based on the analysis of competency data of elementary school teachers in Gerokgak subdistrict, it was found that 77,97 teachers were competent with very high category. Teacher pedagogical content knowledge mainly influences student learning whereas teacher motivation mainly influences students'interest [11]. [12] Pedagogical competence is primarily concerned with the level of understanding of learners, instructional design, and implementation of learning the diagnosis, evaluation of learning, the development of learners has provided significant support in the form of professional pedagogical teaching.…”
Section: Resultsmentioning
confidence: 99%
“…This research suggests that in order to offer high quality instructions, teachers need profound professional knowledge (Shulman, ) as well as respective motivational orientations (Baumert & Kunter, ; Blömeke, Gustaffson, & Shavelson, ). In fact, Kunter et al () present evidence that in addition to the importance of professional knowledge for student learning, motivational orientations play a major role in sparking students' motivation and interest (see also Keller, Neumann, & Fischer, ). Teacher education programs now face the task of conjointly fostering a profound professional knowledge and respective motivational orientations in order to adequately prepare future teachers, a task that is particularly challenging as knowledge and motivational orientations mutually affect each other in their development (e.g., Möller, Retelsdorf, Köller, & Marsh, ).…”
Section: Introductionmentioning
confidence: 99%